Determinant for customer loyalty in Islamic Banking products and services IN Kota Bharu, Kelantan - Nurafigah Mohd Yunus; Nurafni Balqis Mohamad Riping; Nuraini Helwa Syuhaidah Harnizat; Nuraisyah Atikah Nawawi (2023)
The two (2) basic principles governed by the Islamic banking system are forbidden on payments and collections of interest as well as mutual profit or loss sharing. All activities such as gambling, interest and speculative are strictly prohibited in Islamic law. Due to the fierce competition between the Islamic banking industry and foreign and conventional banks, the offering of various products and services is much needed by the Islamic banking industry to attract customers who comply with Islamic law. Therefore, the main objective of this study is to determine the determinants for customer loyalty in Islamic banking products and services in Kota Bharu, Kelantan. The independent variables in this study are satisfaction, product quality, perceived value, and trust and commitment. This study uses online questionnaires with a target of 384 respondents consisting of residents aged 18 years and above in Kota Bharu, Kelantan. The result shows the significant correlation between customer satisfaction, product quality, perceived value and trust and commitment with the customer loyalty in Islamic banking product and services. This study can help the industry to improve and create better products and services to meet the needs of customers. This study adds significant value by contributing to the body of knowledge in this field.